2021
DOI: 10.3390/medicina57101039
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of KRAS Concomitant Mutations in Advanced Lung Adenocarcinoma Patients

Abstract: Background and Objectives: One of the most frequently mutated oncogenes in cancer belongs to the Ras family of proto-oncogenes, which encode distinct key signaling events. RAS gain-of-function mutations are present in ~30% of all human cancers, with KRAS being the most frequently mutated isoform showing alterations in different cancer types including lung cancer. This study aimed to investigate the incidence of KRAS mutations, and concomitant mutations, in advanced non-small cell lung adenocarcinoma patients. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 35 publications
0
11
0
1
Order By: Relevance
“…These biological diversities can be ascribed to the presence of co-occurring genetic events, to the co-presence of different KRAS gene mutation subtypes and to the mutant KRAS allelic content [ 87 ]. Although the role of KRAS co-occurring mutations remains to be elucidated, it has been described that they may affect treatment responses [ 88 ].…”
Section: Kras and Co-occurring Mutations In Lung Acmentioning
confidence: 99%
See 3 more Smart Citations
“…These biological diversities can be ascribed to the presence of co-occurring genetic events, to the co-presence of different KRAS gene mutation subtypes and to the mutant KRAS allelic content [ 87 ]. Although the role of KRAS co-occurring mutations remains to be elucidated, it has been described that they may affect treatment responses [ 88 ].…”
Section: Kras and Co-occurring Mutations In Lung Acmentioning
confidence: 99%
“…KRAS mutations are mutually exclusive with alterations in other molecular markers such as EGFR , ALK and ROS1 , considered genetic drivers of lung cancer development. However, rare cases (<1%) harboring mutations in both KRAS and these markers have been reported [ 88 ]. In lung ACs, the rate of co-occurring mutations with KRAS alterations is 3.2%, and of the KRAS -mutant cases, 33% [ 88 , 89 ].…”
Section: Kras and Co-occurring Mutations In Lung Acmentioning
confidence: 99%
See 2 more Smart Citations
“…The percentage of KRAS mutant alleles detected in the resistant tumours ranged from 0.4% to 17% [19]. Aside from that, KRAS mutations have been designated to be a driver mutation in cancer, with several publications demonstrating a low allelic frequency of KRAS concomitantly existing alongside other driver mutations such as EGFR [20,21], and it was found that de novo KRAS G12C mutation was present ranging from 0.2% [22] to 1.17% of detected samples (n = 6) [23,24]. Detecting de novo KRAS mutation requires high sensitivity and specificity technology, and it was found that KRAS mutation was absent using droplet digital PCR.…”
Section: Intrinsic Resistance In Krasmentioning
confidence: 99%